2022
DOI: 10.3390/ijms23158253
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probiotic Supplementation during Pregnancy on the Future Maternal Risk of Metabolic Syndrome

Abstract: Probiotics are live microorganisms that induce health benefits in the host. Taking probiotics is generally safe and well tolerated by pregnant women and their children. Consumption of probiotics can result in both prophylactic and therapeutic effects. In healthy adult humans, the gut microbiome is stable at the level of the dominant taxa: Bacteroidetes, Firmicutes and Actinobacteria, and has a higher presence of Verrucomicrobia. During pregnancy, an increase in the number of Proteobacteria and Actinobacteria p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 240 publications
(302 reference statements)
0
11
0
Order By: Relevance
“…Asgharian et al [ 6 ] showed some beneficial effects on glucose metabolism in overweight and obese pregnant women by using probiotic yogurt, whereas no significant differences were found in other studies provided with probiotic capsules[ 3 , 41 , 51 , 54 , 55 ]. A review reported daily consumption of 200 g yogurt containing Lactobacillus gasseri (10 8 CFU/g) for 12 wk significantly reduced abdominal obesity[ 39 ]. According to a study by Homayoni et al [ 56 ], foods are better carriers of probiotics than supplements are.…”
Section: Species Dose Method and Duration Of Probioticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Asgharian et al [ 6 ] showed some beneficial effects on glucose metabolism in overweight and obese pregnant women by using probiotic yogurt, whereas no significant differences were found in other studies provided with probiotic capsules[ 3 , 41 , 51 , 54 , 55 ]. A review reported daily consumption of 200 g yogurt containing Lactobacillus gasseri (10 8 CFU/g) for 12 wk significantly reduced abdominal obesity[ 39 ]. According to a study by Homayoni et al [ 56 ], foods are better carriers of probiotics than supplements are.…”
Section: Species Dose Method and Duration Of Probioticsmentioning
confidence: 99%
“…Synbiotics are a mixture comprising live microorganisms and substrates selectively utilized by host microorganisms that confers a health benefit on the host, which is better than prebiotics alone[ 59 ]. Studies also showed that probiotics and prebiotics (synbiotics) were used to modulate the maternal gut microbiome composition, which might enhance probiotic survival and growth better than probiotics alone[ 39 , 52 ]. A narrative review by Li et al [ 23 ] reported that novel food-processing strategies like enzyme-modified prebiotics and probiotic-fermented natural foods have been developed to enhance the beneficial effects on alleviating metabolic diseases.…”
Section: Species Dose Method and Duration Of Probioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…If these compositions are altered, pregnant women may experience an increase in adipose mass, blood sugar levels, IR, and circulating proinflammatory cytokines, resulting in gestational DM (GDM)[ 49 ]. In patients with GDM, obesity, and T2DM, the relative abundance of SCFA-producing bacteria belonging to the genera Faecalibacterium , Rubinococcus , Roseburia , Coprococcus , Akkermansia , Phascolarctobacterium , and Eubacterium was found to decrease[ 50 ]. Moreover, Liu et al [ 51 ] demonstrated increased hyperlipidemia and fasting blood glucose (FBG) levels and increased relative abundance of Streptococcus , Faecalibacterium , Veillonella , Prevotella , Haemophilus , and Actinomyces species in patients with GDM.…”
Section: Dmmentioning
confidence: 99%
“…Pregnancy, both normal and complicated with diseases, also changes the composition and activity of the GM because of fat mass gain, hormonal changes, and increased release of pro-inflammatory cytokines [ 24 ]. Compared to the state before conception, in pregnancy, the GM is characterized by an increase in bacteria belonging to the phyla Proteobacteria and Actinobacteria, with a simultaneous depletion of the beneficial Roseburia intestinalis and Faecalibacterium prausnitzii [ 25 ].…”
Section: Introductionmentioning
confidence: 99%